2019
DOI: 10.1029/2018jc014862
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Drag in a Seagrass Bed

Abstract: We report direct measurement of drag forces due to tidal flow over a submerged seagrass bed in Ngeseksau Reef, Koror State, Republic of Palau. In our study, drag is computed using an array of high‐resolution pressure measurements, from which values of the drag coefficients, CD, referenced to measured depth‐averaged velocities, V, were inferred. Reflecting the fact that seagrass blades deflect in the presence of flow, we find that CD is O(1) when flows are weak and tends toward a value of 0.03 at the highest ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…The drag coefficient C D is calculated using (3) (Figure 4 (a)) and it represents the total momentum loss between 279 mooring sites LT1 and LT3. The total BTPG is the dominant term that balances the drag in the momentum budget, 280 similar to other studies in the coastal regions (e.g., Lentz et al, 2017;Rogers et al, 2018;Monismith et al, 2019).…”
supporting
confidence: 73%
“…The drag coefficient C D is calculated using (3) (Figure 4 (a)) and it represents the total momentum loss between 279 mooring sites LT1 and LT3. The total BTPG is the dominant term that balances the drag in the momentum budget, 280 similar to other studies in the coastal regions (e.g., Lentz et al, 2017;Rogers et al, 2018;Monismith et al, 2019).…”
supporting
confidence: 73%
“…Channel curvature can also cause flow separation of the along-channel velocity at the inside of bends, which is observed at sharp channel bends in both rivers (e.g., Ferguson et al, 2003) and tidal channels (e.g., Leeder & Bridges, 1975). The bend sharpness is customarily quantified as R/w, the ratio of bend radius of curvature In addition to bottom roughness, larger scale features can increase drag on the flow including coral reefs (e.g., Kunkel et al, 2006;Lentz et al, 2017;Rogers et al, 2018), vegetation (e.g., Kadlec, 1990;Monismith et al, 2019;Nepf, 1999), and form drag from topography (e.g., S. J. Warner & MacCready, 2014).…”
Section: Sinuous Tidal Channelsmentioning
confidence: 99%
“…In addition to bottom roughness, larger scale features can increase drag on the flow including coral reefs (e.g., Kunkel et al, 2006; Lentz et al, 2017; Rogers et al, 2018), vegetation (e.g., Kadlec, 1990; Monismith et al, 2019; Nepf, 1999), and form drag from topography (e.g., S. J. Warner & MacCready, 2014). This research will characterize a type of form drag, in particular on how channel meanders can increase the effective drag at larger scales.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to estimate the drag effects from reefs which have been found to be up to 10× greater than the canonical 0.0025 value for muddy or sandy sea beds (Monismith, 2007). Furthermore, Monismith et al (2019) found that the drag from seagrass beds can range from 0.05 to 1 depending on the phase of the tide.…”
Section: Sources and Effects Of Tidal Creek Dragmentioning
confidence: 99%